Geochemical characterization of thermal waters in the Calientes Geothermal Field, Tacna, South of Peru - Cruz Pauccara, Vicentina (2010)
The Calientes Geothermal Field is located in the Western Cordillera of the Andes in southern of Peru, in the Tacna Region at an altitude of 4400 m.a.s.l. inside of volcanic systems with presence of several tectonic structures. In Calientes we can distinguish two volcanic chains aligned of N-S, on the extreme west of the valley there is volcanic complex Yucamane-Calientes-Yucamane Chico, whereas to the extreme east there are volcanic centers aligned to NESW that have presented activity possibly does more than 4 Ma. The mean lithology is andesitic lava interlayered with some porphyritic lavas and sequences of pyroclastic flows. The Calientes Field is characterized for present a several quantity of geothermal manifestations as hot springs. In October 2007, we realized the study of thermal waters with geochemical methods for interpretation their chemical and isotopic characteristics. The thermal waters in Calientes have discharge temperatures in the range of 50°C to 87°C, near neutral pH of 6.90 to 8.34 and conductivity between 1160 to 5920 µS/cm. The geochemical interpretation of the results by means of the use of Langelier and Pipper diagrams shows that thermal waters are classified into the alkali-chloride waters field, rich in Na and Cl ions. The Cl-SO4-HCO3 triangular diagram shows that most of the geothermal waters are close to the chloride corner, typical of geothermal deep fluids. In binary diagram B-Cl we have noticed that waters of Calientes Field presents high concentration of B (Boron) and high relation in the proportion B/Cl, which might indicate that to deep levels the reaction of the water is producing with the sedimentary marine rocks. The d18O vs dD diagram shows that thermal waters are product of mixing meteoric waters with magmatic fluids. The chemical geothermometry in liquid phase allowed us to estimate the temperature to depth of the geothermal resource in Calientes Field. According the results, the temperatures values estimated have a range from 240 ºC to 280°C.